2018
DOI: 10.1093/ageing/afy147
|View full text |Cite
|
Sign up to set email alerts
|

Impact of social care supply on healthcare utilisation by older adults: a systematic review and meta-analysis

Abstract: Objectiveto investigate the impact of the availability and supply of social care on healthcare utilisation (HCU) by older adults in high income countries.Designsystematic review and meta-analysis.Data sourcesmedline, EMBASE, Scopus, Health Management Information Consortium, Cochrane Database of Systematic Reviews, NIHR Health Technology Assessment, NHS Economic Evaluation Database, Database of Abstracts of Reviews of Effectiveness, SCIE Online and ASSIA. Searches were carried out October 2016 (updated April 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 19 publications
0
47
0
Order By: Relevance
“…The synthesis of evidence from studies of social care availability and supply is reported elsewhere (Spiers et al, ). Studies of social care quality were omitted from the review due to inconsistency in how this was defined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of evidence from studies of social care availability and supply is reported elsewhere (Spiers et al, ). Studies of social care quality were omitted from the review due to inconsistency in how this was defined.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence was mapped onto these four domains with separate syntheses intended for each. The synthesis of evidence regarding the availability and supply of social care is reported elsewhere (Spiers et al, ). This paper reports the synthesis of studies examining the influence of social care utilisation .…”
Section: Introductionmentioning
confidence: 99%
“…intermediate care and respite usage) and record measures which can help understand the care home population and their needs at a population level. A more comprehensive understanding of this area using real, routinely collected data could help support the case for adequate investment in social care services to improve lives [34].…”
Section: Discussionmentioning
confidence: 99%
“…1 A surge in the population of senior citizens who need support is expected by 2050. 2 The demographic structure of the world has deeply changed compared with a hundred years ago; 3 so the population of senior citizens is growing. 4 Currently, more than five million Iranian citizens (7.26%) are in their old age, and it is expected that more than 10% of the population in 20 years will be constituted by the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…6 Studies have shown that people's need for healthcare services increases with age. 2 To improve daily care of the elderly and cut the costs of care, we need to collect data about individual's needs. 7 To guarantee proper distribution and use of services for senior citizen, it is essential to comprehensively assess the needs including physical, mental, and social needs.…”
Section: Introductionmentioning
confidence: 99%